The Reality behind the Rhetoric: An Examination of Saudi Vision 2030 Using Imminent Critique - Rachman, Muhammad Fauzi Abdul (Universitas Muhammadiyah Yogyakarta, 2019)
The Saudi Vision 2030 is a Saudi statement of intent to transform the economic structure of Saudi Arabia from oil-based exports to a more skill-based economy. This paper conducted a critical review of the statement, comparing the stated intent of the Saudi authorities with the political situation in the country and region. It was found that given the present power structure, which the government has no intention of changing, the vision is unlikely to be successfully implemented. One of the strongest points in this Vision concerns human development of skills needed in the new order. However, the overt of human right violations within the regime would make realizing the full potentials of its citizens difficult. In particular, the misogynistic policy of denying half its population equal rights would neglect the potential of half of its people. Furthermore, the policies of the state directly contravene the rights and freedoms of people and of other countries in the region as proclaimed in the Vision. This state, then, would be extremely unlikely to fulfil its Vision unless it begins to recognise the basic human rights of all of its citizens. In other words, the Saudi regime would need to adopt less dogmatic policies for the Vision to have any chances of succeeding.